A new species of frog from the Caribbean island of Montserrat (Eleutherodactylidae, Eleutherodactylus) - Hedges, S. Blair (Zootaxa, 2022)
I describe a new species of frog, Eleutherodactylus montserratae sp. nov., from Montserrat, previously confused with E. johnstonei Barbour. It is native to that island and has been introduced, and established, on other Lesser Antillean islands west of 62 degrees west longitude including Anguilla, St. Martin/St. Maarten, St. Barthélemy, Saba, St. Eustatius, St. Christopher, and Nevis, as well as Bermuda. Previous chromosome and molecular studies have shown that populations from these islands are distinct from E. johnstonei, a species occurring east of 62 degrees west longitude in the Lesser Antilles, and elsewhere, but could not identify diagnostic morphological differences. Here, I show that the new species differs morphologically in being smaller (males and females) and having a proportionately larger tympanum, a wider head, and greater separation between the nostrils. Both species have been introduced within and outside of the Caribbean region and will likely expand their ranges in the future.